A survey on osmotic fragility of erythrocytes in plateau population - Aiping WANG; Zhuoga LABA; Wei LI; Xuanzhi WANG; Ruolan TAN; Zhi PU; ZhiJuan LIU; Xuzhen QIN (Zhongguo shuxue zazhi, 2024)
Objective To study the changes in erythrocyte osmotic fragility(EOF) in patients with hypercythemia, polycythemia and anemia under a high altitude environment. Methods A total of 174 outpatients, inpatients and people undergoing physical examination in Tibet Autonomous Region People′s Hospital in October 2020 were enrolled and divided into four groups according to hemoglobin levels: the polycythemia group(n=42), the physiologic increase group(n=48), the anemia group(n=29) and the healthy control group(n=55). They were compared with 67 anemia patients and 67 healthy people in the laboratory of Peking Union Medical College Hospital in the same period as the plain control group. The classic EOF test method was used to compare the results of each group′s EOF. The concentrations of NaCl solution for starting hemolysis (STH) and NaCl solution for complete hemolysis (CTH) were included, and the data were statistically analyzed by SPSS software. Results There was a significant difference in CTH between Zang and Han healthy people (P<0.05). STH in high altitude polycythemia group(0.52) was higher than that in high altitude healthy control group(0.48) (P<0.001). Compared with plain, the median CTH of plateau anemia group(0.36) and plateau health control group(0.36) was significantly higher than that of plain anemia group(0.28) and plain control group(0.28) (P<0.001). Multivariate logistic regression analysis showed that plateau region, female polycythemia and anemia were risk factors for STH elevation. Conclusion This study finds that the EOF increases in the plateau population and patients with polycythemia, which provides reference for studying red blood cell disorders and blood transfusion strategy in the plateau region.